2022
DOI: 10.1101/2022.12.06.519395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SOS1 and KSR1 modulate MEK inhibitor responsiveness to target resistant cell populations based on PI3K and KRAS mutation status

Abstract: KRAS is the most commonly mutated oncogene; targeted therapies have been developed against mediators of key downstream signaling pathways, predominantly components of the RAF/MEK/ERK kinase cascade. Unfortunately, single-agent efficacy of these agents is limited both by intrinsic and acquired resistance. Survival of drug-tolerant persister cells within the heterogeneous tumor population and/or acquired mutations that reactivate RTK/RAS signaling can lead to outgrowth of tumor initiating cells (TICs) and drive … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 141 publications
1
14
0
Order By: Relevance
“…The effect of SOS1 inhibition on trametinib resistance was similarly RTK-PI3K pathway dependent, as PIK3CA comutations ablated the ability of SOS1 inhibition to limit osimertinib resistance. The importance of RTK-PI3K signaling to both osimertinib (51,56) and trametinib (52) resistance reinforces the hypothesis that LUADs are RTK/RAS pathway addicted (57)(58)(59)(60)(61). Our findings that pan-RTK inhibition, via blocking SHP2, SOS1, or SOS2, blocks resistance to two distinct RTK/RAS pathway inhibitors in LUAD suggests that inhibiting proximal RTK signaling may be general strategy to limit resistance to RKT/RAS pathway inhibitors in LUAD (61).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The effect of SOS1 inhibition on trametinib resistance was similarly RTK-PI3K pathway dependent, as PIK3CA comutations ablated the ability of SOS1 inhibition to limit osimertinib resistance. The importance of RTK-PI3K signaling to both osimertinib (51,56) and trametinib (52) resistance reinforces the hypothesis that LUADs are RTK/RAS pathway addicted (57)(58)(59)(60)(61). Our findings that pan-RTK inhibition, via blocking SHP2, SOS1, or SOS2, blocks resistance to two distinct RTK/RAS pathway inhibitors in LUAD suggests that inhibiting proximal RTK signaling may be general strategy to limit resistance to RKT/RAS pathway inhibitors in LUAD (61).…”
Section: Discussionsupporting
confidence: 79%
“…In another study, we found that SOS1 inhibition with BI-3406 ( 55 ) both enhanced the efficacy of and limited the development of acquired resistance to the MEK inhibitor trametinib in KRAS G12 -mutatated LUAD cells ( 52 ). The effect of SOS1 inhibition on trametinib resistance was similarly RTK-PI3K pathway dependent, as PIK3CA co-mutations ablated the ability of SOS1 inhibition to limit osimertinib resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to SOS2, SHP2 and SOS1 are RTK signaling intermediates and potential therapeutic targets whose inhibition might limit resistance to RTK/RAS pathway inhibitors in LUAD. In two parallel sets of studies, we found that inhibition of proximal RTK signaling via (i) the SHP2 inhibitors RMC-4550 or SHP099 significantly inhibited osimertinib resistance in EGFR -mutated LUAD cells (Sealover, Theard et al, submitted) and (ii) the SOS1 inhibitor BI-3406 significantly inhibited MEK-inhibitor resistance in KRAS G12 -mutatated LUAD cells ( 69 ). Based on these data, we propose that inhibition of proximal RTK signaling could be a common mechanism to prevent resistance to targeted therapies in a majority of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SOS2 KO, inhibition of proximal RTK signaling via the SHP2 inhibitors RMC-4550 or SHP099 significantly inhibited osimertinib resistance in EGFR -mutated LUAD cells ( 30 ). The SOS1 inhibitor BI-3406 significantly inhibited acquired resistance to the KRAS G12C ( 71 ) or MEK ( 72 ) inhibitors in KRAS G12 -mutatated LUAD cells. Based on these data, we propose that inhibition of proximal RTK signaling could be a common mechanism to prevent resistance to targeted therapies in a majority of LUAD.…”
Section: Discussionmentioning
confidence: 99%